Odpowiedzi

2010-04-13T16:21:56+02:00
{2X - y - 5 = 0
{3x = y - 6

2x-5=y
3x-2x+5=-6

x=-11
y=-22-5=-27
_________________

{x + 4y - 14 = 0
{3x - y = 20

x=14+4y
42+12y-y=20
11y=-22
y=-2
x=14-8=4
5 3 5
Najlepsza Odpowiedź!
2010-04-13T16:31:26+02:00
Y=(-5)+2x
3x=y-6

y=(-5)+2x
3x={(-5)+2x}-6

y=(-5)+2x
x=(-11)

y=(-5)-2*(-11) -->*-mnożnie
x=(-11)

y=17
x=(-11)

b) x+ 4y -14=0
3x-y=20

x+ 4y -14=0
y=20-3x

x+ 4*(20-3x) -14 =0
y=20-3x

-11x=(-66) :-11
y=20-3x

x=6
y=20-3*6

x=6
y=2
3 3 3
2010-04-13T16:33:57+02:00
1)
2x-y-5=0
3x=y-6

2x-y=5
-y=-3x-6 /* (-1)

2x-y=5
y=3x+6

2x-(3x+6)=5
y=3x+6

2x-3x-6=5
y=3x+6

2x-3x=5+6
y=3x+6

-x=11 /* (-1)
y=3x+6

x=-11
y=3*(-11)+6

x=-11
y=-33+6

x=-11
y=-27


2)
x+4y-14=0
3x-y=20

x+4y=14
3x-y=20

x=-4y+14
3*(-4y+14)-y=20

x=-4y+14
-12y+42-y=20

x=-4y+14
-13y=-22 /: (-13)

x=-4y+14
y=22/13

x=-4*(22/13)+14
y=22/13

x=88/13+14
y=22/13

x=270/13
y=22/13


Jak będzie coś źle to sory ;] Ale powinno być Ok ;)
(nie jestem pewna co do tego 2)
2 4 2